Importance of Promyelocytic Leukema Protein (PML) for Kaposi’s Sarcoma-Associated Herpesvirus Lytic Replication - Hossain, Md. Golzar; Ohsaki, Eriko; Honda, Tomoyuki; Ueda, Keiji (Frontiers in Microbiology, 2018)
Many DNA virus replication-related proteins are associated with promyelocytic leukemia protein (PML), a component of nuclear domain 10 (ND10), which has been investigated for its potential involvement in viral replication. In the case of Kaposi’s sarcoma-associated herpesvirus (KSHV) lytic gene products, K8 (K-bZIP), ORF59 and ORF75 have been shown to colocalize with PML, but its importance in KSHV lytic replication is still unclear. In this study, we analyzed the functional influence of PML on KSHV latency and lytic replication in KSHV-infected primary effusion lymphoma (PEL) cell lines. Stable PML-knockout (BC3-PMLKO) and PML-overexpressing BC3 cells (BC3PML) were successfully generated and the latency and reactivation status were analyzed. The results demonstrated that neither KSHV latency nor the episome copy number was affected in BC3-PMLKO cells. In the reactivation phase, the expression dynamics of KSHV immediate-early or early lytic proteins such as RTA, K9 (vIRF1), K5, K3, ORF59 and K8 (K-bZIP) were comparable between wild-type, control BC3 and BC3-PMLKO cells. Interestingly, KSHV lytic replication, virion production and expression of late genes were downregulated in BC3-PMLKO cells and upregulated in BC3PML cells, compared to those in control or wild-type BC3 cells. Moreover, exogenous PML increased the size of the PML dots and recruited additional K8 (K-bZIP) to PML-NBs as dots. Therefore, PML would function as a positive regulator for KSHV lytic DNA replication by recruiting KSHV replication factors such as K8 (K-bZIP) or ORF59 to the PML-NBs.